Comorbidity of COVID-19 related Fatalities in Tertiary Care Hospitals of Rawalpindi, Pakistan - Rizwana Shahid ,Muhammad Umar ,Raja Bilal Zafar ,Shazia Zeb ,Saima Ambreen ,Muhammad Omar Akram (Journal of Rawalpindi Medical College, 2020)
Objectives: To assess the COVID-19 associated fatalities with respect to demographics, comorbidity, critical illness, and length of hospital stay in tertiary care hospitals. Subjects & Methods: A retrospective hospital data-based research was done among 216 COVID-19 associated mortalities registered in 4 tertiary care hospitals Holy Family Hospital (HFH), Benazir Bhutto Hospital (BBH), District Head Quarters Hospital (DHQ) and Rawalpindi Institute of Urology & Transplantation (RIU & T) affiliated with Rawalpindi Medical University from 29th March-15th June 2020. The data was gathered by consecutive sampling pertinent to demographics, hospital stay, comorbidity, critical illness, and ventilator or oxygen support. The length of hospital stay among fatalities with and without comorbidity was compared by an independent sample z-test. Data were analyzed by using SPSS version 25.0. Results: Of the total 216 COVID-19 related mortalities, 150(69.4%) were males and 66(30.6%) were females. The mean age of fatalities was 55.66 ± 13.97 years. About 76.7% of dying males were 41-70 years old while 56.1% of females dying of COVID-19 were 41-60 years old. Most (60.8%) of study subjects had hypertension followed by diabetes (53.8%), Ischemic Heart Disease (17.5%), and respiratory disorders (12.3%). About 75% of the critically ill patients needed a ventilator for respiratory support. Length of hospital stay was determined to have a statistically insignificant association (P > 0.10) with the presence or absence of comorbidity among COVID-19 patients. Critical illness had a highly significant association (P < 0.000) with ventilator support among COVID-19 related mortalities. Conclusion: People 41-70 years should preferably adopt stringent precautions for protection against COVID-19. Comorbid states chiefly hypertension, diabetes, cardiac and respiratory diseases need special consideration amid COVID-19 pandemic to abstain from adverse health outcomes.